A tunable detection range of ion-selective nano-optodes by controlling solvatochromic dye transducer lipophilicity. Issue 83 (2nd October 2019) - Wang, Lu; Bakker, Eric
Abstract : A range of ionic solvatochromic dye (SD) transducers for use in ion-selective emulsified optical sensors are introduced and characterized. Abstract : A range of ionic solvatochromic dye (SD) transducers for use in ion-selective emulsified optical sensors are introduced and characterized. They share the same chromophore group, ( E )-4-(4-(dimethylamino)styryl)pyridinium, but vary in their lipophilicities by grafted alkyl or ethoxy groups. The calibration curve is found to shift by a total of 2.7 orders of magnitude with the lipophilicity of the SD.